Plan de negocios para la producción y exportación de mermelada a base de polvo de cacao, combinada con ron y naranja, al mercado estadounidense - Espinoza Rodríguez, Ambar Nicool (2018)
This investigation develops a "Business plan for the production and export of jam based on cocoa powder, combined with rum and orange, to the US market". It begins development the justification of the research is established, then in the analysis of environments, evidence that in the United States there is a favorable environment for the introduction of a jam produced from organic cocoa powder, combined with rum and orange because Ecuadorian cocoa is recognized worldwide and most people seek products that promote their health, additionally states that the industry is attractive. The analysis of the client shows the behavior of the potential market, it is appreciated that to enter the US market requires a different sales proposal, quality and an appropriate price; It is concluded that there is a real business opportunity for the craft production of the product and its export to the United States, because in Los Angeles CA it is possible to market 338,485 units in the first year only considering a 2% of potential market capture. The general marketing strategy will be of differentiation, it is expected to deliver a product according to market demands, with unique characteristics and qualities: artisanal, high quality organic raw material, exotic flavor combination, ecological packaging and significant added values. Miski's value offer focuses on satisfying consumer needs, differentiating itself from the competition and delivering added value to the target market. Misk'i operations will be based on ethics, responsibility, knowledge, excellence and efficient processes, and will be oriented towards leadership. When evaluating the project and investor flows, through the financial indicators VAN, TIR and PRI, favorable values are obtained, so it is concluded that the business is feasible and profitable.